A loop-loop "kissing" complex is the essential part of the dimer linkage of genomic HIV-1 RNA. - Paillart, J C (1996)
RNA-RNA interactions govern a number of biological processes. Several RNAs, including natural sense and antisense RNAs, interact by means of a two-step mechanism: recognition is mediated by a loop-loop complex, which is then stabilized by formation of an extended intermolecular duplex. It was proposed that the same mechanism holds for dimerization of the genomic RNA of human immunodeficiency virus type 1 (HIV-1), an event thought to control crucial steps of HIV-1 replication. However, whereas interaction between the partially self-complementary loop of the dimerization initiation site (DIS) of each monomer is well established, formation of the extended duplex remained speculative. Here we first show that in vitro dimerization of HIV-1 RNA is a specific process, not resulting from simple annealing of denatured molecules. Next we used mutants of the DIS to test the formation of the extended duplex. Four pairs of transcomplementary mutants were designed in such a way that all pairs can form the loop-loop "kissing" complex, but only two of them can potentially form the extended duplex. All pairs of mutants form heterodimers whose thermal stability, dissociation constant, and dynamics were analyzed. Taken together, our results indicate that, in contrast with the interactions between natural sense and antisense RNAs, no extended duplex is formed during dimerization of HIV-1 RNA. We also showed that 55-mer sense RNAs containing the DIS are able to interfere with the preformed HIV-1 RNA dimer.